Cuantificación de la biomasa y del carbono almacenado en las especies comerciales de un bosque de colina alta del divisor del distrito de Pampa Hermosa, Loreto. 2022 - Velasquez Vallles, Oliver (2024)
With the objective of quantifying the biomass and carbon stored and determine the difference between both variables in commercial species of a high hill forest of Sierra Divisor in the district of Pampa Hermosa, Ucayali, in two cutting plots (1 and 4), of the CC "Montes de los Olivos" in a total area of 2712.0131 ha. There are 3534 trees in PC1 and 6142 trees in PC4, with 19 botanical families and 45 commercial species. PC1 has a volume of 15,698 m3/ha, a total biomass of 22530,199 Kg/ha and carbon stock of 11,255 tC/ha, with Cedrelinga catenifformis (Ducke) Ducke having the largest volume (2,737 m3/ha), total biomass (3728,468 Kg/ha) and carbon stock (1,858 tC/ha), and, the diameter class from 120 cm to more contains the highest total biomass (4586,312 Kg/ha) and carbon stock (2,289 tC/ha), and, PC4 has a volume of 15.8654 m3/ha, a total biomass of 23226.31 Kg/ha and carbon stock of 11.558 tC/ha, with Otoba parvifolia (Markgr,) A,H, Gentry having the highest volume (4.629 m3/ha), (5298,289 Kg/ha) and carbon stock (2,601 tC/ha), and, in diameter class from 60 cm to 69,999 cm it contains the highest total biomass (4414,951 Kg/ha) and carbon stock (2,115 tC/ha). The chi-square test indicates that there is a significant difference between total biomass and carbon stocks in commercial species. The study reveals high quantification of total biomass and carbon stocks in commercial species. The work provides information on quantifying biomass and carbon oriented ecosystem services in the Amazon.